Magnetic resonance imaging deformation-based segmentation of the hippocampus in patients with mesial temporal sclerosis and temporal lobe epilepsy - Hogan, Robert E. (Springer-Verlag, 2000)
We compared manual and automated segmentations of the hippocampus in patients with mesial temporal sclerosis. This comparison showed good precision of the deformation-based automated segmentations.